PEREMPUAN DAN AGAMA DALAM NOVEL INDONESIA - Maman Mahayana (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
In Indonesian literature, there have emerged novelist women who give much influence. Along time, they throughdevelopment, both on theme and structure of those texts. Recently, however, precisely post-New order era, Indonesian novelist womenhaven't yet come out from their own problems. They still emphasize gender problems that became issue as struggle against maleestablishment. These struggles realized at questioning to religion and culture. These two domain became their criticism target because bothmade women imprisoned at their own life